The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1002/jcp.1041330320
|View full text |Cite
|
Sign up to set email alerts
|

Human bronchial epithelial cells synthesize cholesterol sulfate during squamous differentiation in vitro

Abstract: Epithelial cells of the airways can, under pathological conditions, undergo squamous metaplasia. The accumulation of cholesterol sulfate has recently been described as a new marker for squamous cell differentiation in rabbit tracheal epithelial cells. We now report that normal human bronchial epithelial cells in culture metabolically incorporated [35S]-sulfate and [3H]-mevalonate into material indistinguishable from cholesterol sulfate by the criteria of solubility in organic solvents, behavior on ion-exchange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…Cholesterol sulfate is present in various tissues and body fluids, and it accumulates during squamous cell differentiation in the epithelial cells of barrier tissues, such as the respiratory tract and esophageal mucosa (11,12,42). Cholesterol sulfate is also found in considerable quantities in the skin, predominantly in the epidermis (10), where it acts as an important regulator during the formation of the epidermal barrier (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cholesterol sulfate is present in various tissues and body fluids, and it accumulates during squamous cell differentiation in the epithelial cells of barrier tissues, such as the respiratory tract and esophageal mucosa (11,12,42). Cholesterol sulfate is also found in considerable quantities in the skin, predominantly in the epidermis (10), where it acts as an important regulator during the formation of the epidermal barrier (42).…”
Section: Discussionmentioning
confidence: 99%
“…Assuming that Mincle may be an important sensor of tissue damage, we performed a search for new endogenous ligands of this receptor. Using chromatography and mass spectrometry, we found that cholesterol sulfate, an abundant molecule in the epithelial barrier layers in the skin and gastrointestinal and respiratory tracts (10)(11)(12), is selectively recognized by Mincle. Here, we show that Mincle activation by cholesterol sulfate causes the secretion of a range of proinflammatory mediators and that s.c. injection of cholesterol sulfate results in a Minclemediated induction of a severe local inflammatory response.…”
mentioning
confidence: 99%
“…However, when these cells are cultured on feeder layers, a subpopulation of type A cells is maintained (140)(141)(142). Tracheobronchial epithelial cells in monolayer culture appear largely to behave like population B cells (64,86,87,143 (145). Diacylglycerol, the endogeneous activator of protein kinase C, produces many of the same effects reported for phorbol esters (146).…”
Section: Phorbol Estersmentioning
confidence: 87%
“…In the multistep program of squamous cell differentiation proposed in Figure 2 retinoids affect very specific stages of squamous differentiation whereas other stages are insensitive to retinoids. Retinoids do not block the commitment to terminal cell division in tracheobronchial or epidermal cells induced by confluence, withdrawal of EGF and insulin or addition of TGF-P or PMA (43,64,73); however, retinoids do block the expression of the differentiated phenotype. Retinoids inhibit the induction of transglutaminase type I (54,(99)(100)(101)(102) and cholesterol sulfotransferase activities, inhibit the accumulation of cholesterol sulfate (63)(64)(65)(66), and inhibit cornification in several in vitro tracheobronchial and epidermal cell systems (39,43,(103)(104)(105) (115,116).…”
Section: Action Of Retinoidsmentioning
confidence: 87%
See 1 more Smart Citation